2019
DOI: 10.3389/fimmu.2019.02402
|View full text |Cite
|
Sign up to set email alerts
|

Growth Restriction and Systemic Immune Development in Preterm Piglets

Abstract: Background: Many preterm infants are born with growth restriction (GR) following maternal or fetal complications before birth. Such infants may continue to grow slowly after birth, regardless of birth weight (BW), due to morbidities related to their immature organs. Severe GR increases the susceptibility to infections, but it is not clear if this is a consequence of impaired systemic immunity or other factors, such as prolonged hospital stay or poor mucosal barrier function. Using preterm pigs as models for pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 38 publications
3
26
0
Order By: Relevance
“…Cord blood of FGR and NBW pigs was initially used to examine immune competence at birth by a whole blood stimulation assay with LPS. Before LPS stimulation, FGR preterm pigs showed lower baseline expressions of few genes, However, we did not measure the leucocyte levels in Exp 1, but we have previously shown that FGR piglets tend to have lower lymphocyte counts (but not neutrophil and monocyte counts) in cord blood (10). Therefore, it is possible that differences in expressions of some lymphocytes-related genes at baseline may be influenced by the leucocyte levels.…”
Section: Discussionmentioning
confidence: 89%
See 4 more Smart Citations
“…Cord blood of FGR and NBW pigs was initially used to examine immune competence at birth by a whole blood stimulation assay with LPS. Before LPS stimulation, FGR preterm pigs showed lower baseline expressions of few genes, However, we did not measure the leucocyte levels in Exp 1, but we have previously shown that FGR piglets tend to have lower lymphocyte counts (but not neutrophil and monocyte counts) in cord blood (10). Therefore, it is possible that differences in expressions of some lymphocytes-related genes at baseline may be influenced by the leucocyte levels.…”
Section: Discussionmentioning
confidence: 89%
“…Collectively, our results suggest that preterm pigs born moderately growth restricted were immune suppressed or experienced some delay in immune maturation, which may be further exacerbated by neonatal antibiotic use. Such effects may be most pronounced in the immediate neonatal period (e.g., the first 1-2 weeks), as supported by the limited effects of moderate FGR and prematurity on blood immune parameters (10,53) and gut and brain development beyond the first 2 weeks of life (53,54). Correspondingly, a dysfunctional immune system and an increased risk of infections in preterm infants with fetal growth restriction suggest special care and medical attention in this population to avoid damaging infections in the critical neonatal period.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations